1996
DOI: 10.1002/chin.199622024
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Bismuth Germanate.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
5
2
Order By: Relevance
“…Yukhin et al reported that a crystallized BGO powder can be formed by the dispersion of Bi 6 O 5 (OH) 3 (NO 3 ) 5 (H 2 O) 3 in an ammonium germanate solution between 333 and 363 K at a pH of 8 to 10. This phenomenon was explained as being the direct result of interaction between the solid Bi 6 O 5 (OH) 3 -(NO 3 ) 5 (H 2 O) 3 and aqueous ammonium germanate; 5) however, this same reaction is found in the present study to proceed even at room temperature at pH ≥ 3.1. In the previous reports, 5,12) there was no experiment or discussion on the intermediate states between the initial state and the final BGO formed state.…”
Section: Phases Formed In As-precipitated Samplescontrasting
confidence: 52%
See 3 more Smart Citations
“…Yukhin et al reported that a crystallized BGO powder can be formed by the dispersion of Bi 6 O 5 (OH) 3 (NO 3 ) 5 (H 2 O) 3 in an ammonium germanate solution between 333 and 363 K at a pH of 8 to 10. This phenomenon was explained as being the direct result of interaction between the solid Bi 6 O 5 (OH) 3 -(NO 3 ) 5 (H 2 O) 3 and aqueous ammonium germanate; 5) however, this same reaction is found in the present study to proceed even at room temperature at pH ≥ 3.1. In the previous reports, 5,12) there was no experiment or discussion on the intermediate states between the initial state and the final BGO formed state.…”
Section: Phases Formed In As-precipitated Samplescontrasting
confidence: 52%
“…4) As a result, the synthesis of BGO powder is an important aspect of single-crystal fabrication. [4][5][6][7][8][9][10][11] The low-temperature synthesis of single-phase BGO powder has been hindered by the fact that any significant decrease in the synthesis temperature leads to impurities even when using a sol-gel method. 4,[8][9][10][11] Therefore, a temperature between 1123 and 1283 K is necessary for synthesis in air.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that Bi 6 O 5 (OH) 3 (NO 3 ) 5 (H 2 O) 3 transits into BGO when dispersed in a germanium-containing ammonia solution for 30 min and then heated to 520 °C. [32] Similarly, in [33] a suspension of Bi(NO 3 ) 3 and GeO 2 is exposured at 70 °C and pH = 2.5 (it is achieved by periodic addition of an ammonia solution) for a few hours during which bismuth germanate gradually precipitates. The reaction is considered to have reached its end when addition of ammonia resulted in a rise in the pH to 5.…”
Section: Resultsmentioning
confidence: 99%